2023
DOI: 10.3390/ijerph20032340
|View full text |Cite
|
Sign up to set email alerts
|

How Confinement and Back to Normal Affected the Well-Being and Thus Sleep, Headaches and Temporomandibular Disorders

Abstract: The COVID-19 pandemic is having negative consequences not only for people’s general health but also for the masticatory system. This article aimed to assess confinement and its new normal impact on well-being, sleep, headaches, and temporomandibular disorders (TMD). An anonymous survey was distributed to a Spanish university community. Participants completed a well-being index (WHO-5), a questionnaire related to sleep quality (the BEARS test), a headache diagnostic test (the tension type headache (TTH) and mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…These E-ISSN: 2821-2738 interventions, potentially addressing issues such as rumination, proved effective in reducing the frequency of headaches in patients suffering from both migraines and TTH, thus improving their overall quality of life. Rosales Leal et al (2023) examined the effects of confinement on headache symptoms. Their findings revealed that while confinement did not exacerbate symptoms of temporomandibular disorders (TMD), it negatively influenced overall well-being, sleep quality, and the frequency of TTH and migraines (Leal et al, 2023).…”
Section: E-issn: 2821-2738mentioning
confidence: 99%
See 1 more Smart Citation
“…These E-ISSN: 2821-2738 interventions, potentially addressing issues such as rumination, proved effective in reducing the frequency of headaches in patients suffering from both migraines and TTH, thus improving their overall quality of life. Rosales Leal et al (2023) examined the effects of confinement on headache symptoms. Their findings revealed that while confinement did not exacerbate symptoms of temporomandibular disorders (TMD), it negatively influenced overall well-being, sleep quality, and the frequency of TTH and migraines (Leal et al, 2023).…”
Section: E-issn: 2821-2738mentioning
confidence: 99%
“…Rosales Leal et al (2023) examined the effects of confinement on headache symptoms. Their findings revealed that while confinement did not exacerbate symptoms of temporomandibular disorders (TMD), it negatively influenced overall well-being, sleep quality, and the frequency of TTH and migraines (Leal et al, 2023). This suggests the role of stress and potentially rumination in the aggravation of headache symptoms.…”
Section: E-issn: 2821-2738mentioning
confidence: 99%